Histological And Histochemical Study Of Hypothalamus In Adults New Zealand RabbitsThe hypothalamus is a crucial part of the brain responsible for regulating key physiological functions related to homeostasis and behavior. Due to its significance, it has g - Al-Mansour, Najlaa Awaied; Hussein, Bahaa Fakhri (Journal of Neonatal Surgery, 2025)
The hypothalamus is a crucial part of the brain responsible for regulating key physiological functions related to homeostasis and behavior. Due to its significance, it has garnered interest from neuroscientists aiming to better understand how its subregions connect with other parts of the central nervous system. This study utilized ten adult New Zealand rabbits, from which hypothalamic tissue samples were collected. The specimens were treated and stained with Hematoxylin and Eosin (H&E), in addition to a specialized stain for further analysis. The objective of this investigation was to provide a detailed histological analysis of the hypothalamus and its various nuclei in adult New Zealand rabbits. Tissue samples were prepared for microscopic examination using light microscopy. The findings revealed that the hypothalamus in these rabbits consists of five nuclei: the paraventricular (PVN), anterior (AN), dorsomedial (DN), ventromedial (VN), and posterior (PN) nuclei. The paraventricular nucleus is located bilaterally next to the third ventricle, consisting of neurons of diverse morphologies, organized in clusters and irregular formations interlaced with nerve fibers, neuroglial cells, and blood capillaries. The anterior nucleus, located near the optic chiasma, consisted of predominantly large neurons interwoven with nerve fibers. The dorsomedial and ventromedial nuclei were centrally located within the hypothalamus and contained small, rounded to oval neurons. The posterior nucleus, found near the mammillary body, was primarily composed of large, fusiform neurons